2004
DOI: 10.1159/000081948
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Quinupristin-Dalfopristin against Methicillin-Resistant <i>Staphylococcus aureus</i> and Vancomycin-Insensitive <i>S. aureus</i> in a Model of Hematogenous Pulmonary Infection

Abstract: Background: Quinupristin-dalfopristin (Q-D) is a mixture of quinupristin and dalfopristin, which are semisynthetic antibiotics of streptogramin groups B and A, respectively. Methods: We compared the effect of Q-D to that of vancomycin (VCM) in murine models of hematogenous pulmonary infections caused by methicillin-resistant Staphylococcus aureus (MRSA) and VCM-insensitive S. aureus (VISA). Results: Treatment with Q-D resulted in a significant decrease in the number of viable bacteria in the lungs of mice in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In the VISA study, while vancomycin had little effect on bacteriological analysis and survival rate, SMP-601 protected mice against fatal pneumonia and resulted in a significant reduction in mortality. We previously showed that linezolid, the first oxazolidinone agent, DQ-113 and DX-619, novel quinolone agents, and quinupristin-dalfopristin, a complex of streptogramin A and B, are also effective against MRSA and VISA in this model, while vancomycin repeatedly shows little effect (6,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the VISA study, while vancomycin had little effect on bacteriological analysis and survival rate, SMP-601 protected mice against fatal pneumonia and resulted in a significant reduction in mortality. We previously showed that linezolid, the first oxazolidinone agent, DQ-113 and DX-619, novel quinolone agents, and quinupristin-dalfopristin, a complex of streptogramin A and B, are also effective against MRSA and VISA in this model, while vancomycin repeatedly shows little effect (6,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 84%
“…The method of inoculation was described previously (6,8,(12)(13)(14). Briefly, for the MRSA study, NUMR101 was cultured overnight on MuellerHinton II agar plates at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However with the growing problem of antibiotic resistance, interest in this antibiotic has been renewed and new derivatives of virginiamycin have been developed, such as dalfopristine. Synercid, a 70/30 combination of dalfopristin/quinupristin has been used against Staphylococcus aureus and Staphylococcus epidermidis resistant to methycillin and Enterococcus faecium resistant to vancomycin, which are Gram positive bacteria particularly important in nosocomial infections [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the efficacy of antibacterial agents and the pathogenesis of blood-borne staphylococcal pneumonia, we previously established a new murine model of pulmonary infection with S. aureus by intravenous injection of bacteria enmeshed in agar beads [5][6][7][8]. The aim of the present study was to evaluate the activity of DX-619 against pulmonary infection caused by MRSA and VISA compared with vancomycin (VCM) using the above model.…”
Section: Introductionmentioning
confidence: 99%